Social Efficiency of Sectoral Employment in Polish Regions - Magdalena Cyrek (Institute of Economic Research (IER), 2017)
Research background: Regions that are able to use their resources in the most efficient way could be perceived as valuable benchmarks when shaping socio-economic policy. The efficiency, however, can be related not only to pure economic categories but to social goals as well. These two dimensions: economic and social overlap and often have some common stems, among which sectoral structure of employment seems to be an important one. Purpose of the article: The aim of the study was to compare thesocial efficiency of employment in three sectors in Polish voivodeships. Not only were we evaluating therelative performance of each region but we were also paying attention to theefficiency of engagement of human resources in agricultural, industrial and service sectors. Methodology/methods:We adopted DEA method to assess thesocial efficiency of Polish regions. We evaluated social cohesion concerning its two output dimensions: positive, that could be described by social activity and negative, that could be reflected in a form of social exclusion stemming from material sources. We took into account a level of employment in agricultural, industrial and service sectors as inputs in the model and thus focused our attention on thethreesectoral structure of regional economies. Our model assumed non-radial developmental paths and was input oriented (NR-CCR). Data were describing the 16 Polish voivodeships in the2015 year and were extracted from the Central Statistical Office of Poland's databases. Findings& Value added:The conducted research indicate that Polish regions which were the most efficient in terms of social integration were simultaneously those with the best economic results in terms of GDP per capita. The highest social efficiency was characteristic for employment in theservice sector, while the lowest - for agriculture. Thus, structural development appears to be favourable for regional economies also in terms of social cohesion, which is often neglected in the literature.
Keywords: D61; E24; I31; J21; O11; O15; R11; R15; 330; social efficiency; employment; three sectors; regions